Elevated total cholesterol: Its prevalence and population attributable fraction for mortality from coronary heart disease and ischaemic stroke in the Asia-Pacific region - Woodward, M.; Martiniuk, A.; Ying Lee, C.; Lam, T.; Vanderhoorn, S.; Ueshima, H.; Fang, X.; Kim, H.; Rodgers, A.; Patel, A.; Jamrozik, K.; Huxley, Rachel (Sage Publications Ltd., 2008)
Background: About half of the world s cases of cardiovascular disease occur in the Asia-Pacific region. The contribution of serum total cholesterol (TC) to this burden is poorly quantified. Design: The most recent nationally representative data on TC distributions for countries in the region were sought. Individual participant data from 380 483 adults in the Asia Pacific Cohort Studies Collaboration were used to estimate associations between TC and cardiovascular disease. Methods: High TC was defined as =6.2mmol/l, and nonoptimal TC as = 3.8mmol/l. Hazard ratios for fatal coronary heart disease (CHD) and ischaemic stroke (IS) were found from Cox models. Sex-specific population attributable fractions for high TC and nonoptimal TC were estimated for each country. The former used conventional methods, based on single measures of TC and a fixed dichotomy of risk strata; the latter took account of the continuous positive association between TC and both CHD and IS and regression dilution. Results: Data were available from 16 countries. Where reported, the prevalence of high TC ranged from 4 to 27%. The fraction of fatal CHD and IS attributable to high TC ranged from 0 to 14% and 0 to 15%, respectively. Although leaving the relative ranking of countries much the same, the fractions estimated for nonoptimal TC were typically at least twice as big, ranging from 0 to 47% and 0 to 35%, respectively. Conclusion: Conventional methods for estimating disease burden severely underestimate the effect of TC. Cholesterol-lowering strategies could have a tremendous effect in reducing cardiovascular deaths in this populous region. © 2008 The European Society of Cardiology.